Dynamic changes in soil moisture in three typical landscapes of the Heihe River Basin - Gou, Qianqian; Guo, Wenting; Li, Yuda; Liu, Jing; Wang, Guohua (Frontiers in Environmental Science, 2022)
In this study, we selected three typical landscape gradients in the upper, middle, and lower reaches of the Heihe River Basin and used an environmental measuring system to continuously monitor the dynamic of soil moisture from different landscapes. The results showed that (1) The soil moisture content in the growing season was significantly higher than that in the non-growing season in the upper and middle reaches, whereas the lower reaches showed a reverse pattern. (2) There are significant differences in the distribution of soil moisture at various depths of soil profiles from each landscape. As soil depth increased, the soil moisture in the upper reach decreased; deep depths (120-160 cm) constituted water storage depths in the non-growing season, whereas these depths were subjected to water consumption during the growing season. The soil moisture content in the mid-reach increased first, then decreased, and reached its highest level at 40-60 cm; soil moisture content in the lower reach decreased. (3) The coefficient of variation of soil moisture in the upper and middle reaches decreased with an increase in soil depth, whereas the lower reaches showed a reverse trend. (4) Since the implementation of the Heihe river water diversion plan, soil moisture content in both the upper and middle reaches has increased, but that of the lower reach has fluctuated and declined, especially during the growing season. These results imply that the lower reaches of the Heihe River may need additional water transfers during the growing season.